Model Pembelajaran Problem Solving Dan Korelasinya Terhadap Kemampuan Berpikir Kritis Siswa - Maya Amelia Putri; Putri A.L Simbolon (Journal Evaluation in Education (JEE), 2022)
Research objectives: This study aims to obtain the results of the analysis of the implementation of the Problem Solving learning model and its correlation to students' critical thinking skills and to see the relationship between the implementation of the model and the critical thinking skills of class XI students of SMKN 3 Jambi City on thermochemical material. Methodology: This research is a correlational type of quantitative research. The sample was determined by a simple random sampling technique by means of a lottery. The research instrument was in the form of an observation sheet consisting of an observation sheet on the implementation of the Problem Solving model and students' critical thinking skills and posttest on student learning outcomes. The data were analyzed to see the correlation between the implementation of the Problem Solving model on students' critical thinking skills by using the Product Moment correlation test and the significance test using the t test. Main findings: The results of the study prove that there is a correlation between the implementation of the Problem Solving model on students' critical thinking skills. The novelty of this research is to represent the relationship of two variables, namely the use of problem solving models with students' critical thinking skills. Novelty This Research: This study shows that the problem solving learning model has a significant relationship with critical thinking skills. Therefore, it is recommended to use this model in learning.